First record of Curvella sikkimensis (Reeve, 1850) (Pulmonata: Subulidae: Subulininae) from Nepal and its reproductive organs - Budha, Prem Bahadur (Nepalese Journal of Biosciences, 2017)
The genus Curvella contains about 50 described species from the tropical world. Out of them four species are known from north eastern India. The original descriptions of all known species are based on the shell characters only. The reproductive anatomy of any species of the genus is still unknown. This is the first evidence on the reproductive anatomy on Curvella sikkimensis from Nepal.